Metabolite Profiling and Bioactivity Assessment of Antioxidant and Antibacterial Properties in Bulb Fractions of Eleutherine bulbosa (Mill.) Urb - Nurma Angeliani Komalasari; Natalia Natalia Marbun; Gustini Syahbirin; Laksmi Ambarsari; Purwatiningsih Sugita (Jurnal Jamu Indonesia, 2026)
Eleutherine bulbosa is known to contain diverse secondary metabolites with pharmacological potential. This study aimed to identify the bioactive compounds in the ethanol, n-hexane, and unsaponified n-hexane fractions of E. bulbosa bulbs and evaluate their antioxidant and antibacterial activities. The bulbs were extracted using ethanol, followed by n-hexane fractionation and saponification. Antioxidant activity was determined using the DPPH assay, and antibacterial activity was assessed against Staphylococcus aureus and Escherichia coli using the disc diffusion method. LC-MS/MS and GC-MS analyses identified compounds such as eleutherol, resveratrol, coniferaldehyde, and stigmasterol. The ethanol fraction exhibited the highest antioxidant activity (IC₅₀ = 47.54 ± 0.03 mg/L), while the unsaponified n-hexane fraction showed the strongest antibacterial effect (inhibition zone = 16.12 ± 0.16 mm). These findings confirm the potential of E. bulbosaas a natural source of antioxidant and antibacterial agents.